A Treatable Genetic Disease Caused by CAD Mutation - Peng, Xia; Xia, Li-ping; Zhang, Hai-ju; Zhang, Jing; Yu, Shi-qian; Wang, Shun; Xu, Yu-ming; Yao, Baozhen; Ye, Jingping (Frontiers in Pediatrics, 2022)
Type 50 early infantile epileptic encephalopathies, or EIEE-50 for short, is an autosomal recessive genetic disorder resulting from CAD mutations. So far, little has been reported on the disease. In this paper, we will discuss the case of a male infant who is eight years and five months old. A whole-exome sequencing of the boy revealed CAD compound heterozygous mutations. He suffered from global developmental delay and regression, refractory epilepsy and anemia. After his diagnosis, we used uridine treatment and gained encouraging results. In this article, we will analyze our case studies in the context of the literature, so as to improve pediatricians’ understanding of the disease.